2023
DOI: 10.3390/s23156656
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Content Detection In Transparent Containers: A Benchmark

Abstract: Various substances that possess liquid states include drinking water, various types of fuel, pharmaceuticals, and chemicals, which are indispensable in our daily lives. There are numerous real-world applications for liquid content detection in transparent containers, for example, service robots, pouring robots, security checks, industrial observation systems, etc. However, the majority of the existing methods either concentrate on transparent container detection or liquid height estimation; the former provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In [25], Hongliang Li et al demonstrated a liquid recognition scheme based on the vision transformer network, which combines an optical flow-controlled refractive index sensor with visual intelligence algorithms and does not require a spectrometer and precise metasurface mediation, further demonstrating the role of the vision transformer network in liquid-state detection. In addition, You Wu et al [26] proposed a dataset for detecting liquid content in transparent containers (LCDTC), leading to an innovative task involving transparent container detection and liquid content estimation. The dataset proposed by the author developed two baseline detectors, called LCD-YOLOF and LCD-YOLOX, and further proposed a Swin Transformer Integration (WISTE) method for automatically identifying the water index of water bodies.…”
Section: Related Workmentioning
confidence: 99%
“…In [25], Hongliang Li et al demonstrated a liquid recognition scheme based on the vision transformer network, which combines an optical flow-controlled refractive index sensor with visual intelligence algorithms and does not require a spectrometer and precise metasurface mediation, further demonstrating the role of the vision transformer network in liquid-state detection. In addition, You Wu et al [26] proposed a dataset for detecting liquid content in transparent containers (LCDTC), leading to an innovative task involving transparent container detection and liquid content estimation. The dataset proposed by the author developed two baseline detectors, called LCD-YOLOF and LCD-YOLOX, and further proposed a Swin Transformer Integration (WISTE) method for automatically identifying the water index of water bodies.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, the constant λ is used as the weight coefficient to represent the loss for the prediction head of common human postures. We follow [47,83,84] to provide the definitions of these losses below:…”
Section: Chp-yolofmentioning
confidence: 99%
“…However, task-based optimization is needed to determine the appropriate parameters for the best performance. In the research based on the combination of depth vision and liquid level, Do Chau [27], Cheng DF [28], and Wu Y [29] carried out related research, but the casting performance and flexibility need to be improved. Audio information can partially compensate for the lack of visual information and enhance the generalization ability of robot pouring skill.…”
Section: Introductionmentioning
confidence: 99%